Factors Analysis Associated With Villagers Satisfaction of Plan of Hadi: Case Study of gharagol Village of Diwandareh county - moslem savari; nematolah SHIRI; HOSSAIEN shabanalifami (مسکن و محیط روستا, 2013)
Abstract One of the most important structural elements in the development of rural residential areas in support of the poor and reduction of rural vulnerability can be a special attention that should be paid to physical aspects of human social, economic and environmental activities. Nowadays, rural guide plan as the first national comprehensive effort for organizing our country’s villages is counted as the most important tool for rural development management. Rural guide plan is one of the rural development projects that can have a fundamental role in an integrated development of rural areas. Conductor design with the aim to provide context and guidance rural revitalization in terms of social, economic, physical and environmental justice by providing appropriate facilities, It is intended to provide well-suitable for villagers While this is a positive and lasting impact on the project, there is serious doubt In some rural areas have no adverse impact to the satisfaction of the villagers has. Thus, satisfaction of the villagers and the factors that are influential in this regard is very important. In this regard, the main purpose of this study was analysis factors analysis associated with villager’s satisfaction of guide plan in Diwandareh County (Kurdistan Province). The statistical population of this study consisted of all was villagers households gharagol village of Diwandareh county. Using Cochran's formula 81 households by simple random sampling method were selected. The research has been carried out based on descriptive-analytical method and the data has been gathered by questionnaire. The main instrument of the study was a questionnaire which its validity was confirmed by a panel of experts and its reliability was established by calculating Cronbach Alpha Coefficient (α>0.7). Data were analyzed by SPSSWin18 software in two parts of descriptive and inferential statistics. Results showed that the satisfaction of the majority (86.5%) of villagers toward of Guide Plan was low and moderate. In addition, factor analysis, three factors: “create Interest to the village”, “Effects of physical” and “creation sub-employment in village” identified as the effects of guide plan. Results of correlation analysis showed that there was positive and significant relationship between of the majority of existing components in guide plan with villagers satisfaction of its. Finally, based on the results of the study, in order to improve the effects of rural guide plan on social, economic, physical and environmental aspects of rural areas, a number of recommendations and guidelines for rural development managers, planners and policy makers were presented.